2020
DOI: 10.1002/cey2.57
|View full text |Cite
|
Sign up to set email alerts
|

Anode materials for potassium‐ion batteries: Current status and prospects

Abstract: Potassium‐ion batteries (KIBs) as one of the most promising alternatives to lithium‐ion batteries have been highly valued in recent years. However, progress in KIBs is largely restricted by the sluggish development in anode materials. Therefore, it is imperative to systematically outline and evaluate the recent research advances in the field of anode materials for KIBs toward promoting the development of high‐performance anode materials for KIBs. In this review, the recent achievements in anode materials for K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 132 publications
(243 reference statements)
0
50
0
Order By: Relevance
“…[ 293–295 ] However, the reversible capacity and cycling stability of the state‐of‐the‐art ZIBs are quite inferior compared with LIBs, and the researches of heterostructures still remain in a primary stage, but the current results are really inspiring. [ 296,297 ] Xu et al. [ 298 ] reported a MoO 2 /Mo 2 N heterostructure cathode via an electrochemical activation process.…”
Section: The Electrochemical Performance Of Heterostructuresmentioning
confidence: 99%
“…[ 293–295 ] However, the reversible capacity and cycling stability of the state‐of‐the‐art ZIBs are quite inferior compared with LIBs, and the researches of heterostructures still remain in a primary stage, but the current results are really inspiring. [ 296,297 ] Xu et al. [ 298 ] reported a MoO 2 /Mo 2 N heterostructure cathode via an electrochemical activation process.…”
Section: The Electrochemical Performance Of Heterostructuresmentioning
confidence: 99%
“…Previous studies have shown that ions and electrons transport kinetics of electrodes, especially anodes, was considered to be the ratedetermining step of working batteries. 36,37 Accordingly, the construction of suitable anodes is one of the core technologies for designing KIBs with high-rate performance. Specifically, electronic conductivity and ion diffusivity of anodes are two key parameters.…”
Section: Key Parameters For High-rate Performancementioning
confidence: 99%
“…Moreover, the structure-guided approach facilitates the synthesis and fabrication of pure/doped C x N y materials and CNBC's, respectively. The massive attention into CNBMs for electrochemical energy storage and conversion can be attributed to the combination of these two approaches, and they are paramount to the advancement in this field [140,[168][169][170][171][172]. Despite the significant progress made so far in the study of CNBMs for energy storage devices, there are still unresolved issues; therefore, we provide some perspectives to resolve them.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%